Centre of Pressure Detection and Analysis with a High-resolution and Low-cost Smart Insole. (2015) - Tan, Adin Ming; Fuss, Franz Konstantin; Weizman, Yehuda; Azari, Michael F.
Abstract: This study aims to compare the accuracy of a pair of novel low-cost insoles with that of the proven standard Kistler force plate. The correlation of both devices had a r2 value of 0.942 and 0.946 for COPx and COPy respectively during dynamic tests conducted to measure macroscopic changes of the COP. Fractal dimension analysis was conducted to measure minute changes during quiet standing on solid surface and on foam, with both insoles and the force plate showing the same trend where the fractal values of standing on foam were significantly higher than that of standing on a solid surface. Further validation was done to compare the results with the mean velocities of the measured data that showed identical significant trends as the fractal dimension analysis.